2018
DOI: 10.1186/s12544-018-0326-4
|View full text |Cite
|
Sign up to set email alerts
|

Digibus©: results from the first self-driving shuttle trial on a public road in Austria

Abstract: From April to November 2017, the non-profit research organisation Salzburg Research conducted the "Digibus© 2017" trial, the first trial of a self-driving shuttle on a public road in Austria. The shuttle from the French company Navya Tech has been tested on a 1.4-km long track in the village of Koppl, which is situated approximately ten kilometres east from the City of Salzburg. The trial in Koppl was one of the first trials worldwide on public roads with mixed traffic in a rural area. The focus of this trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…A further comparison of the respondents' comments from the Brussels sites to the comments gathered at the Austrian pilot site [33] shows similarities in terms of the aspects of the shuttle and experiences that were liked and disliked. Passengers appreciated the silent and smooth driving behaviour of the vehicle, and they felt safe during the ride.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A further comparison of the respondents' comments from the Brussels sites to the comments gathered at the Austrian pilot site [33] shows similarities in terms of the aspects of the shuttle and experiences that were liked and disliked. Passengers appreciated the silent and smooth driving behaviour of the vehicle, and they felt safe during the ride.…”
Section: Discussionmentioning
confidence: 96%
“…In both studies, respondents' satisfaction with aspects of the shuttle and the availability and professionalism of the accompanying personnel was very positive. Furthermore, in other European pilot studies, the presence of an onboard operator has been remarked to provide an increased feeling of safety for passengers [33]. In a transition period from manually driven to autonomous transport, it can be argued that on-board personnel can serve to inform the passengers and reassure them with their knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researches point out the fact that many automatic systems and sensors that ensure autonomous driving mode operate properly only under optimal weather conditions or during daylight hours [6] (Bartuska, 2020). It is also said that most part of test drives is conducted in sunny weather that is far from reality [7]. A special concern is raised around this issue in Russia since its road and the climatic environment is characterized by extended periods of negative temperatures (up to 8-10 months per year); significant pollutions of road pavement, significant road unevenness causing accidents, and so on [8].…”
Section: Autonomous Vehiclesmentioning
confidence: 99%
“…Until now, only few studies have been conducted that look into the future acceptance of autonomous buses [20,6]. Recent demonstration projects of autonomous buses have shown that passengers feel rather safe in automated buses [5], but, as noted by Rehrl et al [23] this is likely caused by the presence of a human operator, who is required by law during all drives. Rehrl et al also assume that fully 'unaccompanied' buses with higher driving speeds and mixed traffic, as can be expected to be introduced within the next years, will lead to a decrease in the passenger's sense of safety.…”
Section: Introductionmentioning
confidence: 99%